(untitled) (PERcursos Linguísticos, 2024)
ABSTRACT: During the last few years, the number of scientific research and awareness of autism has increased considerably and therefore various methodologies and therapies have been created so that people with autism can be more fully included in society. The decision to investigate autistic communication through the area of Music Therapy is based on the fact that music has proved to be a powerful tool that can facilitate the learning processes of children with autism. Music can enhance their social relationships, and words learned from songs can cross over into real-life applications (Reece, 2024). Therefore, this paper aims to analyze the benefits of Music Therapy and investigate how it can help them at school and through improved communication foster greater advancements in their learning process. KEYWORDS: Music Therapy. Autism. Communication. Learning Methodologies.